State competitiveness and sustainable development in the context of the new educational paradigm - Garashchuk, Olena; Kutsenko, Vira (Herald of Economics, 2021)
Introduction. The article is devoted to the disclosure of an important task that now faces Ukraine, namely, the achievement of the competitiveness of its economy. This should be achieved on the basis of the principles of sustainable development, which is based on maintaining a balance of opportunities for the biosphere, social and economic development in order to meet the needs of the population. At the same time, the social sphere, and above all its educational sector, is of enduring importance.Purpose of the research. Therefore, the purpose of the study presented in this article is to substantiate ways to increase both quantitative and qualitative indicators of the national economy through the implementation of a new educational paradigm, intensification of the countryʼs socio-economic development, and the growth of its competitiveness.Results. Deepening of methodological approaches to identify trends in relation to the impact of the social sphere on ensuring sustainable economic development, achieving the competitiveness of the state in the context of the need for the national economy to enter an innovative growth trajectory.The content component of sustainable socio-economic support is analyzed. The role of education in this process is highlighted. The state of its development and resource provision is characterized. The main factors that contribute to the increase in the production of goods and services on an innovative basis are highlighted. In this regard, the analysis of the current situation in Ukraine regarding the training of highly qualified personnel and the activities of employees performing innovative developments has been carried out.It is proposed to actively introduce a new educational paradigm, new educational technologies that contribute to the growth of not only quantitative, but also qualitative parameters of the social sphere, economy and society as a whole.Prospects. As follows from the practice of economically developed countries, without raising the educational level of the population, it is impossible to ensure the growth of labor productivity, as well as to achieve the active introduction of new technologies in all spheres of production, together with production, together with the efficient use of resources, which is an important condition for the sustainable socio-economic development of our country. Therefore, it is promising to introduce this experience into domestic practice.